EFFECT OF CHEMICAL TREATMENT OF SESAME SEED CAKE ON RUMINAL DRY MATTER AND CRUD PROTIEN DEGRADATION (Journal of Veterinary Medicine and Animal Production, 2022)
Nitrogen and dry matter disappearance of sesame seed cake treated with ethanol (50% and 70%) at 78⁰C and 10% tallow  were estimated. Rumen degradability was carried in three fistulated bulls fed sorghum stover as basal diet with 2 kgs supplemental concentrate  and salt lick stone, three bags (a bag in bull at a time) from each treatment were incubated for 0, 3, 6, 12, 24, 36, and 48 hours.In situ crude protein and dry matter, potential degradability, soluble fraction and effective rumen degradability for treated sesame cake were significantly (P
Keywords: degradation; chemical treatment; sesame; cake